INCREASING THE COMPETITIVENESS OF DOMESTIC PRODUCTION BASED ON THE IMPLEMENTATION OF "INDUSTRY 4.0" (CAHIERS MAGELLANES-NS, 2024)
Increasing the competitiveness of domestic production in the context of digitalization is possible only on the basis of the introduction of "Industry 4.0". In particular, Industry 4.0 is based on the struggle for leadership, in which competitiveness is increased primarily by improving product quality, rather than reducing costs. At the same time, Industry 4.0 contributes to the emergence of groups of closely interconnected, integrated companies, up to the blurring of clear boundaries between them. During the fourth Industrial Revolution, the most important factor in technological development is the integration of digital technologies with all spheres of production. Based on the considered features of "Industry 4.0", three types of smart production are proposed, aimed at increasing the competitiveness of domestic production.